A Survey of Dentists in the Management of Dentine Hypersensitivity: A Questionnaire-based Study - Exarchou, Chrysanthie; Betsani, Ioanna; Sakellari, Dimitra; Chatzopoulou, Dominiki; Gillam, David (European Journal of Dentistry, 2019)
Objective Previous studies have indicated that dentists may be uncertain about the etiology, diagnosis, and effective management of dentine sensitivity/dentine hypersensitivity (DH). The purpose of the present study was to evaluate the knowledge and understanding of Greece-based dental professionals in treating DH.Materials and Methods A 26-item questionnaire was sent to a representative sample of Greek dentists.Results Two hundred thirty questionnaires were originally provided to the participants and of the 210 questionnaires that were returned, 191 questionnaires (90 M; 86 F; mean age 36.26 years [standard deviation: 11.34]) were included for analysis, a response rate of 83% was observed. 39.8% of dentists indicated that 1 in 10 of their patients experienced discomfort from DH with 76.4% of dentists indicating that their patients initiated the conversation on DH. In contrast, 44% of the dentists indicated that they initiated the relevant conversation. 34.9% of dentists indicated that the duration of discomfort lasted up to 3 weeks and 76.4% indicated that DH had an impact on their patients’ quality of life. Incorrect tooth brushing was considered to be a major etiological factor (68.6%) with “air blast” (37.3%) and “probing” (15%) as the main methods for identification. 83.6% of dentists indicated that they were confident in recommending over-the-counter products for home use.Conclusion The results of this study suggest that in terms of knowledge and understanding of DH, there is still confusion concerning some aspects of the diagnosis and management of the condition.
Keywords: etiological factors; dentine hypersensitivity; management; quality of life; questionnaire